Spray-Induced Silencing of Pathogenicity Gene MoDES1 via Exogenous Double-Stranded RNA Can Confer Partial Resistance Against Fungal Blast in Rice - Sarkar, Atrayee; Roy-Barman, Subhankar (Frontiers in Plant Science, 2021)
Over the past years, RNA interference has been used as a promising combat strategy against a wide range of pests and pathogens in ensuring global food security. It involves the induction of highly specific post-transcriptional regulation of target essential genes from an organism, via application of precursor long, non-coding double-stranded RNA (dsRNA) molecules that share sequence-complementarity with the mRNAs of the targets. Fungal blast disease caused by Magnaporthe oryzae is one of the most deadly diseases of rice and wheat incurring huge losses in global crop yield. Till date, the Host Induced Gene Silencing (HIGS) and Virus Induced Gene Silencing (VIGS) aspects of RNAi technology have been successfully exploited in development of resistance against M. oryzae in rice. Spray Induced Gene Silencing (SIGS) is a recent, potential, non-transformative and environment-friendly strategy of pest and pathogen management, where naked or nanomaterial-bound dsRNA are sprayed on the leaves to cause selective knockdown of pathogenicity genes. Although it relies on the ability of the fungal pathogens to uptake sprayed RNA, it's efficiency varies largely across phytopathogens and their genes, targeted for silencing. Here, we report a transient dsRNA supplementation system for targeting MoDES1, a pathogenicity gene from M. oryzae, which is a defense-suppressor of rice. We validate the feasibility of in vivo SIGS and post-uptake transfer of RNA signals to distal plant parts in rice-M. oryzae pathosystem through a GFP-based reporter system. A protocol for efficient silencing via direct foliar spray of naked dsRNA was optimised. As a proof-of-concept we demonstrate the phenotypic impacts of in vitro dsDES1 treatment upon growth, conidiation, ROS-scavenging ability and pathogenic potential of M. oryzae. Further, our extrapolatory dsDES1 spray experiments on wounded leaves and whole rice plants indicate resultant silencing of MoDES1, that conferred significant resistance against the fungal blast disease. The evaluation of primary and secondary host defense responses provides evidence supporting the notion that spray of sequence-specific dsRNA on wounded leaf tissue can cause systemic and sustained silencing of a M. oryzae target gene. For the first time, we establish a transgene-free SIGS approach as a promising crop protection strategy against the notorious rice-blast fungus.